2020
DOI: 10.3389/fgeed.2020.602970
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies and Challenges for CRISPR/Cas9 Mediated Genome Editing of the Mammalian Brain

Abstract: Neurons and glia are highly polarized cells with extensive subcellular structures extending over large distances from their cell bodies. Previous research has revealed elaborate protein signaling complexes localized within intracellular compartments. Thus, exploring the function and the localization of endogenous proteins is vital to understanding the precise molecular mechanisms underlying the synapse, cellular, and circuit function. Recent advances in CRISPR/Cas9-based genome editing techniques have allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…It is also possible to establish mutant mice that enable us to monitor MOP by applying similar genetic manipulation to fertilized eggs and obtaining offspring with the desired gene in a few months. 26 A previous study reported on post‐translational modifications of MOP by mass spectrometry using whole‐brain tissue. 27 Such mutant mice might provide information on the physiological regulation of endogenous MOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to establish mutant mice that enable us to monitor MOP by applying similar genetic manipulation to fertilized eggs and obtaining offspring with the desired gene in a few months. 26 A previous study reported on post‐translational modifications of MOP by mass spectrometry using whole‐brain tissue. 27 Such mutant mice might provide information on the physiological regulation of endogenous MOP.…”
Section: Discussionmentioning
confidence: 99%
“…Using the aforementioned methods to those opioid receptor families might reveal their unknown physiological significance. It is also possible to establish mutant mice that enable us to monitor MOP by applying similar genetic manipulation to fertilized eggs and obtaining offspring with the desired gene in a few months 26 . A previous study reported on post‐translational modifications of MOP by mass spectrometry using whole‐brain tissue 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding potential off-target edits caused by the CRISPR/Cas9 system have been voiced by multiple groups (Zhang et al 2015 ; Modell et al 2022 ). Other concerns such as in vivo payload delivery, immunogenicity, tissue system targeting, and unwanted genetic mosaicism (due to concurrently occurring cell division and genome editing) also remain prominent matters of contention in the scientific community (Mehta and Merkel 2020 ; Nishizono et al 2020 ; Gohil et al 2021 ; Modell et al 2022 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Combined expression studies and electron microscopy reconstructions in new model organisms, map tissue morphological and molecular characteristics to identify neural cell types ( Vergara et al, 2021 ). Additionally, CRISPR/Cas9-mediated genome editing delineates neural gene function in high resolution ( Nishizono et al, 2020 ; Fang et al, 2021 ). Individual researcher groups and consortia deliver large-scale profiling data and cell biology experimentalists are key to functionally dissect them.…”
Section: Mapping Neural Cell Types: From Single Criteria Toward a Mul...mentioning
confidence: 99%